Construction of the New High-Speed Railway Line Ulm–Wendlingen in Karstifed Rock. (2016) - Raithel, Marc; Baumbusch, Jürgen; Kielbassa, Stefan
Abstract: The new railway line from Wendlingen to Ulm (in Southern Germany) is currently under construction. With planned travel speeds of up to 250 km/h the slab track system will be used as track superstructure. The high-speed line is crossing the Swabian Alb, whereby on a distance of about 23 km karstified jurassic terrain is being crossed. After an overview of the project this publication provides information about general problems induced by the construction of a slab track type high-speed railway line on karstified sub-soil. Typical examples of the geophysical karst investigation program and the karst phenomena found in this project are given. Furthermore the static/cyclic FEM-calculations for the proof of relevant cavities are being displayed. The publication is completed by a presentation of particular measures which were used for the strengthening of the subsoil.